2016
DOI: 10.4209/aaqr.2015.08.0528
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Airborne Particles in Indoor Environments: Applicability of Particle Counting for Prediction of Bioaerosol Concentrations

Abstract: Indoor bioaerosols have recently received considerable interest because of their impact on health. In this study, concentrations of bioaerosols in relation to airborne particulate matter in various indoor environments were investigated. The comparative performance of two common biosamplers, including the single-stage Andersen impactor and the all-glass impinger (AGI) for bioaerosol sampling, was also evaluated. The average levels of airborne bacteria and fungi sampled by Andersen were 516 and 176 colony formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 31 publications
4
38
2
Order By: Relevance
“…Table 4 summarize the comparison of the present average bacterial aerosols concentration with other studies. The average concentration of bacterial aerosols (956 cfu/m 3 ) exceeds the value reported by WHO [16] (500 cfu/m 3 ) and other studies by Lee et al [17] and Mirhoseini et al [18]. While the present results are lower than studies of Mentes et al [19] and Pegas et al [20].…”
Section: Resultscontrasting
confidence: 57%
“…Table 4 summarize the comparison of the present average bacterial aerosols concentration with other studies. The average concentration of bacterial aerosols (956 cfu/m 3 ) exceeds the value reported by WHO [16] (500 cfu/m 3 ) and other studies by Lee et al [17] and Mirhoseini et al [18]. While the present results are lower than studies of Mentes et al [19] and Pegas et al [20].…”
Section: Resultscontrasting
confidence: 57%
“…Environmental health studies have indicated that constant exposure to bioaerosols containing high concentrations of bacteria can lead to respiratory diseases including allergies, infections, and other adverse health effect (Bünger et al, 2007;Lu et al, 2016;Mirhoseini et al, 2016). With the current increases in atmospheric pollution, human respiratory systems have been suffering from more health risks both indoors and outdoors when exposed to biological aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to indoor air contaminants is a vital health risk for urban populations because they generally spend more than 80% of time indoors (Mirhoseini et al, 2016). However, with rapid urbanization, people living in countryside tend to migrate to the cities for better work opportunities and livings.…”
Section: Introductionmentioning
confidence: 99%